Bupivacaine Versus Liposomal Bupivacaine For Pain Control - Beiranvand, Siavash; Moradkhani, Mahmoud Reza (Drug Research, 2018)
Local infiltrations and regional blocks have been some of the effective ways employed to manage and control post-operative pain. One of the limitations of administration of local anesthesia drugs in post-operative conditions is its inability to act for a longer period of time. Multi-vesicular liposomes made up of bupivacaine have been progressively used for their increased duration of action. Compared to bupivacaine HCL, local infiltration of liposomal bupivacaine have shown to have a significantly increase the duration and delay in peak plasma concentration. In this article, we attempt to compare liposomal bupivacaine and bupivacaine based on available clinical literatures. Liposomal bupivacaine has been demonstrated to have promising implications in post- operative pain control resulting in increased patient satisfaction; reduced hospital admission and opioid induced adverse events. Clinical studies have identified liposomal bupivacaine to be effective in delivering increased post-operative pain control. The purpose of this review is to give a comprehensive comparison between bupivacaine liposomal and conventional bupivacaine based on reported clinical trials.
Keywords: bupivacaine; bupivacaine liposomal; formulary; pharmacoeconomics